TEACHING ENGLISH IN THE 21ST CENTURY: SHIFTING PARADIGMS IN THE DIGITAL LANDSCAPE - Nathiya M,; Priyadharshini V, Vidneyangel (International Journal of Research -GRANTHAALAYAH, 2026)
In the modern digital era, people tend to notice the significant metamorphosis in the field of education and predominantly in the English Language Teaching (ELT). The technology has fastened with the unimaginable features and breakthroughs in the field of education broadly. The ancient pedagogical methods have steadily advanced into vibrant and technology-oriented methods that offering to the transforming needs of learners in the universe. This research paper continues to expose the shifting paradigms in ELT via scrutinizing the integration of digital tools, hybrid learning environments such as physical and virtual mode and mobile technologies that have revamped both teaching and learning techniques. It explores the expanding influence of blended learning, flipped classrooms and the use of Artificial Intelligence shortly as AI tools include chatbots and some other language learning applications. This paper also emphasis the progressing role of the English teacher from the content deliverer to facilitator and digital expert. The Digital era becomes the dawn of self-governance and independent learning. Additionally, it propagates the difficulties which is relevant to accessibility, digital literacy and value-based considerations in the virtual learning environment. Through dissecting the emerging trends and pedagogical advancements, this paper furnishes a comprehensive perception of how digital technologies are reinterpreting English language education and how it could be utilised in the 21st century learning approaches. This study is comprised in the constructivist and connectivist paradigms, viewing learners as active agents navigating complex digital networks.